Electrochemical forming of composite materials based on zinc and copper oxide - N. M. Tkachyonok; E. B. Cubenko; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
Structures based on ZnO and Cu, which are a polycrystalline composite consisting of crystalline ZnO with a crystallographic orientation of (002) and (101) doped with Cu and crystalline metallic Cu, were obtained by electrochemical deposition on substrates of single crystal origin. In the study of the obtained films by Raman spectroscopy, the forming of crystalline ZnO was confirmed. ZnO 2A1 (LO), also in the spectra of each of the bands present in the 649 cm-1 region, not related to the vibrating lattice modes of the intrinsic crystalline ZnO. It was shown that with an increase in the deposition current density in the range of 2–10 mA/cm2, the concentration of Cu in the material weakens, while the number of Cu clusters decreases, but the degree of doping of ZnO with Cu ions increases. ZnO-based composites exhibit a broad photoluminescence band in the long wavelength range of 500–700 nm, related with vacancies and interstitial oxygen atoms in the crystal lattice. At a current density of 5 mA / cm2, short-wavelength shifts of the photoluminescence bands are observed, due to the doping of Cu, since impurity levels are created in the band gap associated with the presence of Cu in ZnO films. A change in the radiation intensities was observed at a current density of 10 mA/cm2, which is due to the greater thickness of the obtained films. The results can be used to develop the manufacturing technology of optoelectronic and photovoltaic devices, photocatalytic coatings based on ZnO.